Accounting Training for Managing Youth Finances in Kayugeitan Village - Wafik Rofilah; Nur Shihatus Sakinah; Hendri Hermawan Adinugraha; Ade Gunawan; Ria Anisatus Sholihah; Courtois Lorenzo (Yayasan Adra Karima Hubbi, 2023)
Background. The problems of teenagers today are so complex and varied. One of the problems faced by adolescents is poor financial management. They are very consumptive in spending their pocket money. This is influenced by the surrounding environment and lifestyle living. Purpose. The purpose of holding community service activities with the title Accounting training for managing youth finances in Kayugeritan village is to share knowledge about managing finances so that teenagers are not consumptive in meeting their needs in the hope that there will be advantages that can be saved according to their abilities. Method. The method used in this community service activity is in the form of providing training through the practice of making financial plans. Results. The result of this service activity is to increase knowledge related to youth financial management. better and able to manage financial expenses by distinguishing which is a need or just a desire. Conclusion. They tend to buy goods based on basic wants, not because of their needs. Even though managing finances since adolescence is very important, there are still many teenagers who have not been able to manage their finances. This can happen because of the psychological aspects of adolescents who are just growing up and the influence of the outside environment.